Multicultural Based Islamic Religious Education In Indonesia - Mukh Nursikin; Bambang Winardi; Ade Risna Sari; Sri Supiah Cahyati; Andrew Shandy Utama (At-Tarbiyat, 2022)
This article discusses multicultural education in the perspective of Islamic education in Indonesia. Multicultural education is a foundation for starting to accept what the times are, especially in today's modern era, which is all-sophisticated and the culture is entering so quickly, either individually or in groups. Multicultural education is basically not so significant and there are still many education experts who question the explanation. Multicultural education is education that leads to cultural diversity in actualizing social and cultural changes in the community as a whole. Multiculturalism in Indonesia has two opposing potential sides. On the one hand, multiculturalism is a wealth of cultural treasures to be proud of. On the one hand, multiculturalism has the potential for conflict due to the lack of awareness to live together in a state of love and humanity. Multicultural Islamic education becomes the normative basis as the basis for realizing how the educational process in Islam should be managed perfectly. So that the Indonesian people are aware that multicultural education is important.